Kepatuhan protokol kesehatan ditinjau dari persepsi risiko dan kepercayaan publik mahasiswa Universitas Sarjanawiyata Tamansiswa - Ricky Kurniawan; Siti Hafsah Budi Argiati; Sulistyo Budiarto (Jurnal Riset Psikologi, 2022)
This study aims to empirically test compliance with the 5M Health Protocol for the Covid-19 pandemic in terms of risk perceptions and public trust of University of Sarjanawiyata Tamansiswa students. The hypotheses in this study are: 1) There is a positive relationship between risk perception on 5M health protocol compliance, 2) There is a positive relationship between public trust in 5M health protocol compliance, 3) There is a positive relationship between risk perception and public trust in protocol compliance 5M health.The subjects used in this study were students of the University of Sarjanawiyata Tamansiswa. The number of subjects in this study were 100 students. The sampling technique used in this study was purposive sampling. The analytical technique used to test the hypothesis in this study uses independent sample T-test analysis to test the validity.The results of this study indicate that there is a relationship between risk perception on 5M health protocol compliance with a significance level of 0.000 (p<0.05), public trust in 5M health protocol compliance with a significance level of 0.000 (p<0.05) and risk perception. and public trust in compliance with the 5M health protocol with a significance level of 0.000 (p<0.05), this indicates that all proposed hypotheses are accepted. This study resulted in R Square = 0.521 so that it can be stated that the contribution of the effectiveness of risk perception and public trust with 5M health protocol compliance is 52.1% while 47.9 is influenced by other variables not examined in this study.